The nurse-led model of hospice care. (2nd March 2019) - Hickish, Dinah; Roberts, Debbie
Abstract : Background: Palliative care in the UK has become more medicalised over the last 50 years, and it was recognised as a medical speciality in 2004. However, out of financial expediency, an inpatient hospice in North Wales has become nurse-led. Aims: This article considers the history of care of the dying and discusses how nurses are best placed to be masters of care of the dying. Methods: The model of nurse-led care is described in terms of how this innovation in practice has developed, allowing the advanced nurse practitioner role to be extended to an autonomous level of hospice care not practised anywhere else in the UK. Conclusion: The innovation of nurse-led hospice care has secured the future of the hospice, making it fiscally robust and ensuring a sustainable service for the community that it serves.